New Trainers - Hunt, Roderick, 2012; Roderick Hunt, 1986; Alex Brychta, 1986 (UK Oxford university press, 2012)
The ORT New Trainer series is part of the Oxford Reading Tree collection, a structured and widely-used reading program designed to support young readers from early phonics to fluent reading. The "New Trainer" readers are typically targeted at early and emerging readers who are beginning to develop reading fluency and comprehension skills.
H3
Students often range from early emergent readers to fluent readers. Many will be English Language Learners (ELLs), so vocabulary, repetition, and contextual support are key. Teachers may need support in scaffolding comprehension for limited-English-proficient children.
Keywords: Supplementary reading material